Parents' reasons to vaccinate their children aged 5–11 years against COVID-19 in Italy - Napoli, Annalisa; Miraglia del Giudice, Grazia; Corea, Francesco; Folcarelli, Lucio; Angelillo, Italo Francesco (Frontiers in Medicine, 2022)
Objectives The aims of this cross-sectional study were to investigate why parents decide to vaccinate, as well as the determinants, their children aged 5-11 years against COVID-19 in Italy. Methods The survey was conducted from January through May 2022. All parents/guardians  who came in randomly selected days to immunization centers for the administration of the first dose of the COVID-19 vaccine to their child were asked to complete a questionnaire about socio-demographic characteristics, attitudes towards COVID-19 infection and vaccination, reason(s) regarding their decision to vaccinate their child, and source(s) of information. Results A total of 358 questionnaires were collected. Parent’s perception that COVID-19 is a severe illness for the child, assessed using a 10-point Likert scale, was 7.5. The overall mean scores of the risk perception for their child of having the COVID-19 before and after the vaccination were 8.1 and 6.3. A significantly higher parents’ level of risk perception for their child of having the COVID-19 after the vaccination has been observed among those not having a university degree, those with the child having at least one chronic medical condition, and those who perceived that COVID-19 is a severe illness for the child. The mean value of respondent trust in the information provided by the pediatricians on a 10-point scale Likert type was 7.6. Female, not having a university degree, higher perception that COVID-19 is a severe disease, not having received information about the vaccination from pediatricians, and needing information had a significantly higher concern of side effects after the vaccination. The most common reasons for vaccinating their children included wanting to protect the child against COVID-19, to attend the school with less risk, to prevent the transmission to family members, and to practice sport and other activities with less risk. Participants with a university degree were more likely to have vaccinated their child for attending the school and practicing sport and other activities with less risk. Conclusions More publicity should be promoted among parents of children aged 5-11 years which would increase the coverage rates and thus lower the transmission of SARS-CoV-2 and reduce the occurrence of COVID-19.